Karakteristik Populasi Labi-Labi (Amyda cartilaginea Boddaert, 1770) Panenan di Kota Jambi dan Kabupaten Muaro Jambi Provinsi Jambi - Albayudi, Albayudi; Ginting, Sri Mina; Novriyanti, Novriyanti; Putri, Rara Yulia (Jurnal Silva Tropika, 2018)
The asiatic softshell turtle Amyda cartilaginea (Boddaert, 1770) is one of the reptile commodities included in CITES Appendix II with vulnerable status according to IUCN. High market demand for the asiatic softshell turtle impact on the exploitation in the wild, so that harvest be limited by quota. The reseach was aimed to know the population characteristics of the asiatic softshell turtle harvested or traded. The population characteristics such as demographic parameters and another parameters. Research used asiatic softshell turtle that collected by traders or harvested location in Jambi City and Muaro Jambi District from June 2015 until August 2015. The result showed there 3 death occurs asiatic softshell turtle in one traders, it’s because fishing equipment make wound for asiatic softshell turtle. Asiatic softshell turtle harvested as much as 383 dominated by mature male with body weight 5,1 kg - 10 kg, or not recomended for harvested by LIPI as scientific authority because being in optimal reproductive age. From colors of carapace and form of pikun, asiatic softshell turtle suspected many much from water flow or rivers.